2008
DOI: 10.1093/cvr/cvn326
|View full text |Cite
|
Sign up to set email alerts
|

Norfuraneol dephosphorylates eNOS at threonine 495 and enhances eNOS activity in human endothelial cells

Abstract: NF enhances endothelial NO release most likely by promoting specific dephosphorylation of eNOS-Thr495 via PP1 in vitro and may be a promising compound to enhance endothelial function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Cells were cultured to confluence on DMEM culture media (ATCC, Manassas, Virginia) with 10% fetal bovine serum (ATCC, Manassas, Virginia) [17, 18]. These cultures were maintained at 37 °C and 5% CO 2 [19].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured to confluence on DMEM culture media (ATCC, Manassas, Virginia) with 10% fetal bovine serum (ATCC, Manassas, Virginia) [17, 18]. These cultures were maintained at 37 °C and 5% CO 2 [19].…”
Section: Methodsmentioning
confidence: 99%
“…PKC and ROCK are the kinase candidates to target Thr497 under physiological conditions19, while the dephosphorylating phosphatase is not unambiguously identified. There appears to be a consensus in the literature that PP1 type phosphatase acts on phosphorylated Thr497 in eNOS (eNOS pThr497 ) in ECs101121. Surprisingly, the type of PP1 holoenzyme has not been identified yet, although this knowledge is essential to uncover physiological regulatory events in the dephosphorylation of eNOS pThr497 .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports101121 have established that PP1 type enzyme dephosphorylates eNOS pThr497 , however, the mediatory role (direct or indirect) of PP2A or the CaM-dependent PP2B/calcineurin could not be excluded either15.…”
mentioning
confidence: 99%
“…In this regard, we recently reported that arsenite results in an acute decrease in NO production by increasing the phosphorylation of endothelial NO synthase (eNOS) at threonine 497 (eNOS-Thr 497 ; in bovine sequence) [10]. Furthermore, this increased eNOS-Thr 497 phosphorylation was shown to be mediated by the ROS/protein phosphatase 1 (PP1) signaling pathway, suggesting possible crosstalk between ROS and NO in arsenite-derived CVD development [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several sites of phosphorylation, such as eNOS-Ser 1179 , eNOS-Thr 497 , and eNOS-Ser 116 , have been identified and evaluated [14,15]. Among those sites, phosphorylation of eNOS-Thr 497 decreases eNOS activity and NO production [11,15]. Although several kinases have been reported to mediate eNOS-Thr 497 phosphorylation, including AMP-activated protein kinase (AMPK) [16], protein kinase C (PKC) [17,18] and Rho-associated protein kinase (ROCK) [19,20], whether these kinases directly phosphorylate eNOS-Thr 497 has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%